Comparison of Ustad Maulana and Mama Dedeh's Da'wah Strategy: Building Religion in the Era of Globalization through Mass Media - Syarifah, Lailatus; Jannah, Siti Raudhatul; Wazis, Kun (SAINTIS Publishing, 2024)
This study aims to compare the preaching strategies of Ustad Maulana and Mama Dedeh in building religiosity in the era of globalization through mass media. This study examines the preaching strategies of Ustad Maulana and Mama Dedeh in building religiosity through mass media, especially the programs